Aspergillus population diversity and its role in aflatoxin contamination of cashew nuts from coastal Kenya. - Colletah Rhoda Musangi; Bicko Steve Juma; Dennis Wamalabe Mukhebi; Everlyne Moraa Isoe; Cromwell Mwiti Kibiti; Wilton Mwema Mbinda (PLoS ONE)
Cashew nuts are among the main cash crops in coastal Kenya, due in large part to their high nutritional value. Unfortunately, they also make them highly susceptible to mold contamination, resulting in biodeterioration of the nutritional value and potential contamination with toxic secondary metabolites, such as aflatoxins, that cause them to be rejected for sale at the market. We determined the population diversity of the Aspergillus species and their role in aflatoxin contamination in cashew nuts in selected coastal regions of Kenya. Fifty raw cashew nut samples were collected from post-harvest storage facilities across three counties in Kenya's coastal region and examined for moisture content and the presence of Aspergillus fungi. About 63 presumptive isolates were recovered from the cashew nuts. ITS and 28S rDNA regions were sequenced. The aflD, aflM and aflR genes were amplified to identify the potentially aflatoxigenic from the Aspergillus isolates. The Aflatoxins' presence on the isolates was screened using UV and the ammonia vapour test on coconut milk agar and validated using ELISA assay. A comparison of cashew moisture content between the three counties sampled revealed a significant difference. Sixty-three isolates were recovered and identified to section based on morphological characters and their respective ITS regions were used to obtain species identifications. Three sections from the genus were represented, Flavi and Nigri, and Terrei with isolates from the section Nigri having slightly greater abundance (n = 35). The aflD, aflM and aflR genes were amplified for all isolates to assess the presence of the aflatoxin biosynthesis pathway, indicating the potential for aflatoxin production. Less than half of the Aspergillus isolates (39.68%) contained the aflatoxin pathway genes, while 22.22% isolates were aflatoxigenic, which included only the section Flavi isolates. Section Flavi isolates identification was confirmed by calmodulin gene. The presence of species from Aspergillus section Flavi and section Nigri indicate the potential for aflatoxin or ochratoxin in the cashew nuts. The study established a foundation for future investigations of the fungi and mycotoxins contaminating cashew nuts in Kenya, which necessitates developing strategies to prevent infection by mycotoxigenic fungi, especially during the storage and processing phases.